Rural Road Network Decision Model for Hilly Regions of Nepal - Shrestha, Jagat Kumar (Journal of Advanced College of Engineering and Management, 2018)
Transportation cost is one of the major costs for public and private sectors in rural areas of developing countries (in order to deliver goods and services). This is due to the absence of links or to their poor physical conditions (such as road surface in a road network). To reduce the operation costs in existing links better road surfaces are needed. However, only some links can be improved or constructed to the best surface level at the same time, due to resource constraints. Hence, a careful decision about which links should be improved or constructed to achieve the minimum transportation cost is needed. This paper presents a decision support model for a rural road network that provides portfolio of suggested links for road network improvements or constructions and offers solutions for different budget levels minimizing the transportation cost in the rural road network. Mixed integer programming is used to get an optimal solution.